Pengaruh Muhammad Jaidi Sebagai Brand Ambassador Terhadap Brand Image Kopi Lain Hati - Gracia Yoas; Salman Naning (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The use of a brand ambassador for a brand is an action or strategy taken to form a brand image and also build people's mindset toward the brand. The purpose of this study was to determine the effect of Muhammad Jaidi as a Brand Ambassador on the Brand Image of Lain Hati Coffee. Researchers use the VisCAP model to see the aspects contained in a brand ambassador. This study used a quantitative approach and the data obtained came from distributing questionnaires. The data obtained in this study were processed using Product Moment Correlation and Simple Linear Regression. The results of this study conclude that the relationship between brand ambassadors and brand image is strong. Also, Muhammad Jaidi as a brand ambassador influences the Kopi Lain Hati Brand Image. The amount of influence given by Muhammad Jaidi as Brand Ambassador to the Lain Hati Kopi Brand Image is 44.2%.